2004
DOI: 10.1124/jpet.103.061242
|View full text |Cite
|
Sign up to set email alerts
|

δ-Opioid Agonists: Differential Efficacy and Potency of SNC80, Its 3-OH (SNC86) and 3-Desoxy (SNC162) Derivatives in Sprague-Dawley Rats

Abstract: The diarylpiperazine ␦-opioid agonist SNC80 [(ϩ)-4-[(␣R)-␣-[(2S,5R)-2,5-dimethyl-4-(2-propenyl)-1-piperazinyl]-(3-methoxyphenyl)methyl]-N,N-diethylbenzamide] producesconvulsions, antidepressant-like effects, and locomotor stimulation in rats. The present study compared the behavioral effects in Sprague-Dawley rats of SNC80 with its two derivatives,which differ by one functional group located in the 3-position of the benzylic ring. In behavioral measures, these three compounds demonstrated a rank order of poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 9 publications
2
59
1
Order By: Relevance
“…In rodents, deltorphin analogs and other DOR-selective agonists can interfere with motor functions (Longoni et al, 1991, Miaskowski et al, 1991, Negri et al, 1991, Spina et al, 1998, Fraser et al, 2000b, Broom et al, 2002, Jutkiewicz et al, 2004. In the present study, we observed that intrathecal administration of deltorphin II induced a rapid, but transient inhibition of motor capacities, an effect mimicked with SNC80 and reversed by the deltaselective antagonist naltrindole.…”
Section: Discussionsupporting
confidence: 62%
“…In rodents, deltorphin analogs and other DOR-selective agonists can interfere with motor functions (Longoni et al, 1991, Miaskowski et al, 1991, Negri et al, 1991, Spina et al, 1998, Fraser et al, 2000b, Broom et al, 2002, Jutkiewicz et al, 2004. In the present study, we observed that intrathecal administration of deltorphin II induced a rapid, but transient inhibition of motor capacities, an effect mimicked with SNC80 and reversed by the deltaselective antagonist naltrindole.…”
Section: Discussionsupporting
confidence: 62%
“…4a), only one (17%) out of six rats convulsed with 10 mg kg −1 IV SNC80. All convulsions produced by slow infusions appeared similar to typical delta-opioid receptor-mediated convulsions (Broom et al 2002a;Jutkiewicz et al 2004). The dose-effect curve for convulsions was shifted to the right by increasing the duration of i.v.…”
Section: Snc80 Administration By Slow IV Infusionsmentioning
confidence: 81%
“…Thus, minimizing the undesirable convulsive effects while retaining the antidepressant-like properties appears feasible. In particular, the latency to convulsion shortens with increasing the dose of agonist (Broom et al 2002a) and with different routes of administration (Jutkiewicz et al 2004), indicating that the speed with which drug enters the circulation and/or the central nervous system (CNS) may play a role in delta-opioid-mediated convulsions. These preliminary data suggested that it might be possible to alter the time to onset of convulsion and, possibly, other characteristics of this behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, increasing levels of endogenous delta-opioid peptides with enkephalinase inhibitors such as RB101 revealed antidepressant-like effects in both mice and rats (Baamonde et al, 1992;Tejedor-Real et al, 1998). In addition, the nonpeptidic delta-opioid receptor agonists SNC80 ( (+)-4-(alphaR)-alpha-((2S,5R)-4-allyl-2,5-dimethyl-1piperazinyl)-3-methoxybenzyl)N,N-diethylbenzamide) and (+)BW373U86 ((+)-4-[(alpha-R*)-alpha-[(2S*,5R*)-4-allyl-2,5-dimethyl-1-piperazinyl]-3-hydroxybenzyl]-N,Ndiethylbenzamide) to rats elicited naltrindole-sensitive antidepressant-like properties, as assessed in the forced swim test (Broom et al, 2002a;Jutkiewicz et al, 2004;Jutkiewicz et al, 2005). Conversely, chronic administration of the potent, nonselective opioid receptor antagonist naltrexone to humans induced a self-reported mental depression in a placebocontrolled open study (Hollister et al, 1981), suggesting a general role for opioid systems in depression.…”
Section: Introductionmentioning
confidence: 99%